Short and Long Term Repeatability of Saccharin Transit Time in Current, Former, and Never Smokers - Emma, Rosalia; Caponnetto, Pasquale; Cibella, Fabio; Caruso, Massimo; Conte, Gianluca; Benfatto, Francesca; Ferlito, Salvatore; Gulino, Alessandro; Polosa, Riccardo (Frontiers in Physiology, 2020)
Mucociliary clearance (MCC) is a major host defense mechanism protecting the respiratory tract against inhaled toxicants and pathogens. Smoking progressively damages the efficiency of MCC thus contributing to increased susceptibility to respiratory infections. Prolonged MCC transit time caused by chronic smoking can be investigated by saccharin test, but substantiation of its short- and long-term reproducibility are needed. Moreover, it is not known if MCC impairment can be reversed when stopping smoking. Objective of the study is to investigate and compare short (3 days) and long term (30 days) repeatability of baseline saccharin transit time among current, former, and never smokers. Saccharin tests results were analysed in 39 current, 40 former, and 40 never smokers. High levels of short-term and long-term repeatability of saccharin transit time were observed in both current and former smokers. Significant differences in MCCTT were observed among the three study groups (p< 0.0001); the median (IQR) MCCTT being 13.15 (10.24-17.25), 7.26 (6.18-9.17) and 7.24 (5.73-8.73) minutes for current, former and never smokers, respectively. Comparison between current smokers and former smokers was significantly different (p <0.0001). There was no significant difference between former and never smokers. The Saccharin test was well tolerated by all participants. We have shown high level of repeatability in both current and former smokers. MCC impairment can be completely reversed, former smokers exhibiting similar saccharin transit time as never smokers. Measurement of saccharin transit time is a sensitive biomarker of physiological effect for the detection of early respiratory health changes in clinical research.